Response of Immature Oil Palm Growth and CO2 emission on Intercropping System After Replanting - Hariyadi Hariyadi; Purwanto Mohammad Yanuar Jarwadi; Diniaty Rosa; Mulyadi Tri; Kurniawati Ani (International Journal of Oil Palm, 2019)
One of the problems in smallholder oil palm plantations was the financing for replanting and loss of revenues during immature oil palm period. One alternative to the problem was the development of an adaptive plant system through intercropping crops planted among immature oil palm crops. The research was conducted in banjar seminai village, dayun subdistrict, siak regency, Riau Province on May to October 2017. The study used a factorial randomized block design with three replications. Annual crops treatment consists of corn, soybean, eggplant and chili. The results showed that there was positive response of oil palm height on intercropping systems. Corn intercropping plants increased the height of oil palm crops. The intercropping plants had no significant effect on the number of leaf midrib and the width of oil palm canopy. Monoculture oil palm crops without intercropping produced average emissions of 8.78 t CO2 ha-1yr-1. Oil palm intercrop with eggplant and soybean produces the highest CO2 emissions of 10.4 and 10.2 t CO2 ha-¹yr-¹, while oil palm in intercrop with chili produced the lowest CO2 emissions of 8.66 t CO2 ha-1yr-¹.